Adverse effects of fructose on cardiometabolic risk factors and hepatic lipid metabolism in subjects with abdominal obesity. (27th June 2017) - Taskinen, M.‐R.; Söderlund, S.; Bogl, L. H.; Hakkarainen, A.; Matikainen, N.; Pietiläinen, K. H.; Räsänen, S.; Lundbom, N.; Björnson, E.; Eliasson, B.; Mancina, R. M.; Romeo, S.; et al.
Abstract: Background: Overconsumption of dietary sugars, fructose in particular, is linked to cardiovascular risk factors such as type 2 diabetes, obesity, dyslipidemia and nonalcoholic fatty liver disease. However, clinical studies have to date not clarified whether these adverse cardiometabolic effects are induced directly by dietary sugars, or whether they are secondary to weight gain. Objectives: To assess the effects of fructose (75 g day −1 ), served with their habitual diet over 12 weeks, on liver fat content and other cardiometabolic risk factors in a large cohort ( n = 71) of abdominally obese men. Methods: We analysed changes in body composition, dietary intake, an extensive panel of cardiometabolic risk markers, hepatic de novo lipogenesis (DNL), liver fat content and postprandial lipid responses after a standardized oral fat tolerance test (OFTT). Results: Fructose consumption had modest adverse effects on cardiometabolic risk factors. However, fructose consumption significantly increased liver fat content and hepatic DNL and decreased β‐hydroxybutyrate (a measure of β‐oxidation). The individual changes in liver fat were highly variable in subjects matched for the same level of weight change. The increase in liver fat content was significantly more pronounced than the weight gain. The increase in DNL correlated positively with triglyceride area under the curve responses after an OFTT. Conclusion: Our data demonstrated adverse effects of moderate fructose consumption for 12 weeks on multiple cardiometabolic risk factors in particular on liver fat content despite only relative low increases in weight and waist circumference. Our study also indicates that there are remarkable individual differences in susceptibility to visceral adiposity/liver fat after real‐world daily consumption of fructose‐sweetened beverages over 12 weeks. Abstract : Click here to view the Letter to the Editor by Dr. K. L. Stanhope .